Income and Health Impacts of IITA's work in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Ranajit Bandyopadhyay, Plant Pathologist, from Agriculture Research for Development in Africa (IITA) talks about the importance of their work in Africa and what they do. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana convened the 6th Africa Agriculture Science Week from July 15-12 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: https://ccafs.cgiar.org/blogs/aasw6 http://www.fara-africa.org/scienceweek/